Boundary Spanning in a Digital World: The Case of Blockchain - Mulligan, C.; Godsiff, P.; Brunelle, A. (Frontiers in Blockchain, 2020)
Blockchain is a relatively new technology that is often described as “creating trust” or “removing intermediaries”. In this paper, we posit that blockchain is a new form of digitally-enabled boundary spanning that allows co-ownership models for the companies in question. Where companies have traditionally employed humans to act as interfaces to the external world, new digital technologies enable a digitised approach to many corporate operations that require interaction towards the external market and environment within which firms must operate. Blockchain is a special subset of digital technologies in this regard, enabling companies to co-operate to control parts of the market and to internalise transaction costs that until now have been a market function; using blockchain companies effectively create a new transaction boundary that means boundary spanning can be deeply embedded in core business, rather than kept to its periphery. This digitally-enabled boundary spanning is a key attribute of the emerging digital economy. Understanding its implications is of critical importance for economics, business and social science literature.